Assessment of Environmental Radioactivity in Soil Samples from Kathmandu Valley, Nepal (Journal of Nepal Physical Society, 2021)
This study was conducted to determine the amount of naturally occurring radioactivity in the soil of Nepal's Kathmandu valley. The activity of naturally occurring radionuclides was determined in these soil samples using a sodium iodide detector. Activity concentrations of 238U, 232Th, and 40K were found in the range: 32.00-111.38 Bq kg-1, 33.52-130.04 Bq kg-1, and 342.50-897.71 Bq kg-1, respectively. These values are well within the permissible range as recommended by UNSCEAR. The soil samples with the highest activity concentrations were primarily found in the valley's northern region. The activity concentrations were also used to calculate the radiation hazard indices: the mean value obtained were 96.63 nGy hr-1 for Absorbed Gamma Dose Rate in Air, 200.04 Bq kg-1 for Radium Equivalent Activity, the 0.12 mSv yr-1 for Annual Effective Dose, and 0.55 for External Hazard Index. These calculated hazard indices were used to estimate the potential radiological health risk from the soil, and the dose rates associated with it were significantly less than their permissible limit. The overall findings indicate no radiological threat to the population's health in the study area. Additionally, the findings of this study provide baseline information on potential radionuclides that contribute mostly for radiation exposure from natural sources.